PENGARUH PENDAPATAN TERHADAP KESEJAHTERAAN KELUARGA PADA INDUSTRI KONVEKSI DI KAMPUNG BULAK TIMUR DEPOK JAWA BARAT - Abdul Azim Wahbi; Syahrudi Syahrudi; Prasetio Ariwibowo (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2020)
The purpose of this study is to determine how far the level of income affects the welfare of the family in the convection industry in Depok. This research was conducted using a survey method with the method of library (library research) and the field method (Field research) while the data analysis test technique in this study used a correlational approach in the form of regression analysis, product moment correlation analysis, coefficient of determination, and hypothesis testing. The results of this study can be seen that the influence of income on welfare. This is evidenced through the calculation results obtained from the correlation coefficient of 0.891. This shows the effect of income on welfare in the high impact category, the variable family welfare is influenced by 79.4% by the income variable. This is evidenced through the coefficient of determination of 0.794. There is a significant effect between the income variable on the welfare variable. This can be seen through the results of t test analysis in which the value of t is 10.773 and ttable is 2.042. Due to the tcount of 10.773 ttable of 2.042 it can be said that there is a significant influence between income on family welfare.